1990
DOI: 10.3168/jds.s0022-0302(90)78825-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yeast Culture on Nutrient Digestibility and Milk Yield Response in Early- to Midlactation Dairy Cows

Abstract: Twenty Holstein dairy cows in early lactation were allocated equally to one of two treatments on the basis of age, days in milk, and mean daily 2-wk pretrial milk yield. All animals were fed a total mixed ration; the ration for the treatment group was top-dressed with 90 g/d of yeast culture, Saccharomyces cerevisiae. Treatment period lasted 10 wk. Mean daily DM intake, milk production, milk composition, and BW were not significantly affected by treatment. Feed and fecal samples were collected the last 3 d of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
49
1
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 6 publications
12
49
1
2
Order By: Relevance
“…Similarly the enhancement in fat yield was also observed by researches (Moallem et al, 2012Putnam et al, 1997. Arambel and Kent, (1990) attributed ADF in the ration while maintained milk fat synthesis. Similarly some studies have shown that yeast culture had no beneficial effect on milk composition of dairy cows (Arambel and Kent, 1990;Bagheri et al, 2009;Soder et al, 1999;Swartz et al, 1994), but in lactating goats fed live yeast, a reduction in milk fat (Stella et al, 2007) or increase (Giger-Reverdin et al, 1996) have observed.…”
Section: Fatty Acid Profilesupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly the enhancement in fat yield was also observed by researches (Moallem et al, 2012Putnam et al, 1997. Arambel and Kent, (1990) attributed ADF in the ration while maintained milk fat synthesis. Similarly some studies have shown that yeast culture had no beneficial effect on milk composition of dairy cows (Arambel and Kent, 1990;Bagheri et al, 2009;Soder et al, 1999;Swartz et al, 1994), but in lactating goats fed live yeast, a reduction in milk fat (Stella et al, 2007) or increase (Giger-Reverdin et al, 1996) have observed.…”
Section: Fatty Acid Profilesupporting
confidence: 66%
“…Prilled fat feeding during periparturient period and early lactation increased milk yield and milk fat contents in cows (Yadav et al, 2015) and Murrah buffaloes (Shikha et al, 2016) However, some researchers (Arambel et al, 1990) Robinson et al, 1999: Bagheri et al, 2009 reported no beneficial effects of yeast feeding on milk production performance. The increase in fat percentage in the SG group was due to more availability of FAs in blood and their incorporation into milk fat in mammary gland (Shelke et al, 2012).…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…In case none of these DFM survives in the rumen, then their lysis would provide protoplasm, which is a source of nutrients for the rumen microbes (Arambel and Kent, 1990). It is therefore hypothesized that Bl and Cb alone may not directly affect fibre digestibility, but may indirectly stimulate cellulolytic microbes in the rumen through cross-feeding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast culture may also provide stimulatory factors for cellulolytic bacteria, such as B vitamins or branched-chain fatty acids (Weidmeier et al, 1987). On lysis, the yeast cells also provide protoplasm, which is a source of nutrition for the rumen microbes (Arambel and Kent, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Szucs et al (2013) the best yield was reached by the treated primiparous cows but no important difference was found between the daily yield of treated and control multiparous cows. Arambel and Kent (1990) found a little or no response to yeast cultures for the milk yield and milk composition. While others report opposite findings -milk yield decreases in supplementation with live yeast (Bertrand and Grimes, 1997;Schwartz et al, 1994).…”
Section: Discussionmentioning
confidence: 93%